Software Engineering Perspectives and Application in Intelligent Systems Proceedings of the 5th Computer Science On-line Conference 2016 (CSOC2016), Vol 2 - Silhavy, Radek; Senkerik, Roman; Oplatkova, Zuzana Kominkova; Silhavy, Petr.; Prokopova, Zdenka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The volume Software Engineering Perspectives and Application in Intelligent Systems presents new approaches and methods to real-world problems, and in particular, exploratory research that describes novel approaches in the field of Software Engineering. Particular emphasis is laid on modern trends in selected fields of interest. New algorithms or methods in a variety of fields are also presented. The 5th Computer Science On-line Conference (CSOC 2016) is intended to provide an international forum for discussions on the latest research results in all areas related to Computer Science. The addressed topics are the theoretical aspects and applications of Computer Science, Artificial Intelligences, Cybernetics, Automation Control Theory and Software Engineering.
The Effect of Nutrition Education System for Elementary School Students in Nutrition Knowledge -- MATP: A Multi-Agent model for the University Timetabling Problem -- Optimized Clustering with Statistical-based Local Model for Replica Management in DDM over Grid -- The MOBIKEY Keystroke Dynamics Password Database: Benchmark Results -- Joint Algorithm for Traffic Normalization and Energy-Efficiency in Cellular Network -- Model of a Quantum Computer, Architecture and Software Implementation -- MEEM: A Novel Middleware for Energy Efficiency in Mobile Adhoc Network -- A 3D Visualization Design and Realization of Otrokovice in the Nineteen-thirties -- Cost Effective Framework for complex and Heterogeneous Data Integration in Warehouse -- Uplink Channel Performance and Implementation of Software for Image Communication in 4G Network -- A Brief Analysis of Reported Problems in the Use of Function Points -- Task Allocation in Distributed Software Development Aided by Verbal Decision Analysis -- Application of Evolutionary Algorithm in Supply Chain Management for Internet Marketing.-Intelligent Mechanism for Cloud Federation and Requirements Changes Management -- Comparison of the Intrusion Detection System Rules in Relation with the SCADA Systems -- An Optimization Scheduler in the Intranet Grid -- A Hybrid Weight-Based Clustering Algorithm for Wireless Sensor Networks -- On Robust Computation of Tensor Classifiers Based on the Higher-Order Singular Value Decomposition -- Model Checking Mutual Exclusion Algorithms Using UPPAAL.-Software usability Evaluation Based on the User Pinpoint Activity Heat Map -- Inflated Power Iteration Clustering Algorithm to Optimize Convergence Using Lagrangian Constraint -- Virtualization of Operating System Using Type-2 Hypervisor -- A New Game-Theoretical Approach in Network Routing: Algorithms and Their Performance Analysis in OMNeT++ -- Using Analytical Programming for Software Effort Estimation -- Intra-Frame Prediction Mode Decision for Efficient Compression and Signal Quality -- Multidimensional Design of OLAP System for Context-Aware Analysis in the Ambient Intelligence Environment -- A Process for Creating the Elicitation Guide of Non-Functional Requirements -- A Data-Centric Algorithm for Identifying Use Cases -- Algorithm to Balance Compression and Signal Quality using Novel Compressive Sensing in Medical Images -- Application of Virtualization Technology for Implementing Smart House Control Systems -- Utilization of Motion Animation for Analysis of Basic Self-defense Techniques -- EMG Analysis for Basic Self-defense Techniques -- Proposal of the Web Application for Selection Of Suitable Job Applicants Using Expert System -- The technique of Selecting Multiversion Software System Structure with Minimum Simultaneous Module Version Usage -- Expressing Pre- and Post-conditions, Attributesand Business Constraints in Artifact-Centric Business Processes Using Object Role Modeling -- Spam Detection: Naive Bayesian Classification and Rpn Expression-Based Lgp Approaches Compared -- An Agile Approach to Improve Process-Oriented Software Development -- Ad-hoc Routing Protocols Comparison Using Open-Source Simulation Tool -- Discrete Event Simulation of Loading Unloading Operations in a Specific Intermodal Transportation Context -- Parallelization of Fuzzy Logic Analysis for Pattern Recognition -- Performance Management Using Autonomous Control-Based Distributed Coordination Approach in a Volunteer Grid Computing Environment.-Intelligent Speech Interaction of Lifting Devices and their Operators.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Computational Intelligence; Artificial Intelligence; Control and Systems Theory